New Trimethoxybenzamides and Trimethoxyphenylureas Derived from Dimethylcarbazole as Cytotoxic Agents. Part I. (1st May 2014) - Panno, Antonella; Sinicropi, Maria Stefania; Caruso, Anna; El‐Kashef, Hussein; Lancelot, Jean‐Charles; Aubert, Geneviève; Lesnard, Aurélien; Cresteil, Thierry; Rault, Sylvain
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>